Anthropause and Human Behaviour: Contributions from a Situated Educational Neuroscience - Bacigalupe, Maria de los Angeles (Pensando Psicología, 2022)
Objective: We develop a theoretical discussion from our perspective of the situated educational neuroscience, based on the relational anthropology point of view, to generate ambits of discussion in which the educational neuroscience can contribute into the context of COVID-19 pandemic and pospandemic. Subject: The context of the COVID-19 pandemic has made it possible to put in tension issues that were pending on the global agenda. Among these issues, the importance of the human being as part of the ecosystem with which they maintain co-construction relationships is not minor. Situated educational neuroscience is a tool that can bring valuable contributions to the discussion to collaborate in addressing this tension. Development: We organize de argumentation in four sections: 1. The opportunity the anthropause posts to the humankind and its relations with their environment, 2. The role that studies on behaviour and evolution have on this opportunity, 3. The contribution of a situated educational neuroscience as a framework and transdiscipline which works on translational research in this context of pandemics and anthropause, and 4. The succinct presentation of two examples where we argue that a situated educational neuroscience has tools to contribute. Conclusions: We propose conclusions open to discussion where we return to the idea of a situated educational neuroscience which is committed with its context. As an approach or as a transdiscipline with translational research functions, we consider that a situated educational neuroscience contains tools that can contribute to the conversation with other sciences and disciplines and with the empirical knowledge of communities, in order to join efforts to overcome social injustices and move forward as humankind from this current pandemic situation, having acquired strategies of resilience that can serve to deal with other persistent and future situations.